Sequential therapy with supercharged NK cells with either chemotherapy drug cisplatin or anti-PD-1 antibody decreases the tumor size and significantly enhances the NK function in Hu-BLT mice - Kaur, Kawaljit; Chen, Po-Chun; Ko, Meng-Wei; Mei, Ao; Senjor, Emanuela; Malarkannan, Subramaniam; Kos, Janko; Jewett, Anahid (Frontiers in Immunology, 2023)
Introduction and methods In this study we report that sequential treatment of supercharged NK (sNK) cells with either chemotherapeutic drugs or check-point inhibitors eliminate both poorly differentiated and well differentiated tumors in-vivo in humanized-BLT mice. Background and results sNK cells were found to be a unique population of activated NK cells with genetic, proteomic, and functional attributes that are very different from primary untreated or IL-2 treated NK cells. Furthermore, NK-supernatant differentiated or well-differentiated oral or pancreatic tumor cell lines are not susceptible to IL-2 activated primary NK cell-mediated cytotoxicity; however, they are greatly killed by the CDDP and paclitaxel in in-vitro assays. Injection of one dose of sNK cells at 1 million cells per mouse to aggressive CSC-like/poorly differentiated oral tumor bearing mice, followed by an injection of CDDP, inhibited tumor weight and growth, and increased IFN-γ secretion as well as NK cell-mediated cytotoxicity substantially in bone marrow, spleen and peripheral blood derived immune cells. Similarly, the use of check point inhibitor anti-PD-1 antibody increased IFN-γ secretion and NK cell-mediated cytotoxicity, and decreased the tumor burden in-vivo, and tumor growth of resected minimal residual tumors from hu-BLT mice when used sequentially with sNK cells. The addition of anti-PDL1 antibody to poorly differentiated MP2, NK-differentiated MP2 or well-differentiated PL-12 pancreatic tumors had different effects on tumor cells depending on the differentiation status of the tumor cells, since differentiated tumors expressed PD-L1 and were susceptible to NK cell mediated ADCC, whereas poorly differentiated OSCSCs or MP2 did not express PD-L1 and were killed directly by the NK cells. Conclusions Therefore, the ability to target combinatorially clones of tumors with NK cells and chemotherapeutic drugs or NK cells with checkpoint inhibitors at different stages of tumor differentiation may be crucial for successful eradication and cure of cancer. Furthermore, the success of check point inhibitor PD-L1 may relate to the levels of expression on tumor cells.